Increased Residential Clustering of COVID-19 Cases Associated With SARS-CoV-2 Variant of Concern B.1.1.7. Issue 4 (3rd May 2022) - Flannagan, Joe; Twohig, Katherine A.; Carter, Emma; Chudasama, Dimple Y.; Lamagni, Theresa; Dabrera, Gavin
Abstract : Background: The emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) B.1.1.7 variant in England in 2020 and subsequent global spread emphasized the need to understand epidemiologic characteristics of SARS-CoV-2 variants. A diagnostic proxy for this variant, referred to as S-gene target failure, provided a rich dataset to assess transmissibility of the variant in an analysis of clustering in residential settings. Methods: We used a pair-matched case–control study design to estimate odds of onward transmission within households with S-gene target failure index cases versus nontarget failure index cases. We defined cases as the index in a household cluster (clustered case) and controls as a case with no subsequent household cluster (sporadic). We matched clustered and sporadic cases one-to-one on specimen week, geography, and property type. We used conditional logistic regression, adjusting for age, sex, ethnicity, and symptom status, to assess odds of residential clustering. Results: Our study population comprised 57, 244 individuals with specimen dates from 23 November 2020 to 4 January 2021. Crude analysis yielded 54% increased odds (odds ratio [OR] = 1.5; 95% confidence interval [CI] = 1.5, 1.6) of residential clustering associated with S-gene target failure; the association remained in the fully adjusted model (OR = 1.6, 95% CI = 1.5, 1.6). Stratified analyses by region showed increased odds of residential clustering associated with target failure in all regions apart from the Southwest, where we observed lower precision. Similar adjusted odds ratios with precise confidence intervals remained in stratified analyses by property category. Conclusion: We observed increased odds in all property types, consistent with greater transmissibility of the B.1.1.7 variant in this high-risk setting.